Asset Management in the income-earning section of the State Railway of Thailand - Khanphum, Suwat (Journal for Developing the Social and Community, 2022)
This research has three objectives. (1) To analyze the internal and external environment affecting asset management in the income-earning sector of the state railway of Thailand; 2) To analyze the asset management process in the income-earning sector of the state railway of Thailand. 3) To present a model that represents the management of assets in the income-earning sector of the state railway of Thailand. This research is qualitative research. Executives involved in asset management of the state railway of Thailand and employees of the asset Management department of the state railway of Thailand. 20 people collected information from documents, evidence and in-depth interviews. Analyze data with content analysis methods. Findings (1) Environment affecting the asset management of the State Railway of Thailand, such as strategies, rules, regulations, market expansion of land and buildings, economic conditions, political and social, etc. (2) Analysis of the process of asset management is as follows: Planning: there was a plan but not all of them were practical. Maintenance control: The agency was responsible. Distribution and destruction: It is appropriate. (3) A model that represents the management of assets in respect of the income-earning sector of the state railway of Thailand. Consists of (a) Planning: namely the establishment of a responsible agency. Having effective information land development plan and business management model deployment (b) Management: business management, private engagement in management and investment, streamlining operational steps adjustment of personnel management and development and adoption of modern technology (c) Control and maintenance: including clearly defining the details of the lease agreement, the responsible authorities strictly operate and hire skilled private companies. and (d) Distribution and destruction: compliance with regulations, The operation is fast and transparent